ANALYSIS OF ONLINE SHOPPER BEHAVIOR AND MARKETING STRATEGY FOR CAKE PRODUCT (CASE STUDY: TIME TO EAT CAKE) (The Indonesian Journal of Business Administration, 2019)
Indonesia has the potential power to become the largest digital economy. Development of the digital economy as new technologies is an opportunity to access global markets and drive new innovation for the food industry. Therefore, there are three objectives of this study. First, to investigate online shoppers’ behavior toward food product, particularly of cake. Second, to explore the possibility of internet as alternative tools for food distribution channels, particularly of cake. The last is to perform the recommendation online marketing strategy for the business. The study used mixed methods approaches (quantitative and qualitative) to explore different areas of management. The quantitative methods of this study are using the Theory of Planned Behavior. The study was conducted by distributing a survey to online shoppers’ behavior toward food products, particularly of cake in Bandung. Using the final data from 100 respondents, the data was analyzed using Microsoft Excel, SPSS, Factor Analysis, and Multi Linear Regression. The quantitative methods were conducted by interview to gain the information of E-Consumer Decision-Making Process in buying Time to Eat Cake product. Furthermore, this study was used the observation technique to analyze social media content marketing among similar business using the theory of Social Media Marketing. The survey result found that the attitude towards buying, subjective norms, and perceived behavioral control variable have a positive influence on the online shopping intention. The interview result found that consumer obtains Time to Eat Cake information through an Instagram, the reason in buying through an online platform is easy to obtain information, and process of purchasing product. Next, by consumer evaluation, Time to Eat Cake need some improvement in product, price, content marketing, also adding a promotional program, and for the place, the existence offline store is still important for the consumer. For purchase decision, consumers are influenced by friends. The last is post-purchase, the majority of consumer are satistied in buying Time to Eat Cake through an online platform. Furthermore, the observation result found that from several businesses that have been analyzed, almost all businesses have the same content marketing strategy. This research provides input to Time to Eat Cake to develop a mix marketing strategy.Keywords: food industry, cake product, theory of planned behavior, online shopping behavior, decision-making process, social media marketing, mix marketing strategy.